2016
DOI: 10.1071/cp15257
|View full text |Cite
|
Sign up to set email alerts
|

Competition and growth of a grass–legume mixture fertilised with nitrogen and phosphorus: effect on nutrient acquisition, root morphology and symbiosis with soil microorganisms

Abstract: Achieving a fast initial growth is crucial for legumes because grasses grow more rapidly and compete much better with forbs. In a pot experiment with a nutrient-deficient soil, we added nitrogen (N), phosphorus (P) and N + P to pure and mixed stands of Lotus tenuis and Festuca arundinacea and investigated the effects of on plant growth, nutrient uptake and symbiotic associations with arbuscular mycorrhizae and rhizobia. Plant yield, N and P acquisition, mycorrhizal colonisation, rhizobial nodulation and root l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
1
15
0
1
Order By: Relevance
“…Competition is the contentious interaction for limited resources between organisms that is characterized by efficient resource consumption (exploitation) or harmful effects to the adversary (interference) (Ghoul and Mitri, 2016). Competition for nutrients and space is a key form of antagonistic interaction that affects rhizobia and host plants (Postma et al, 1990;Poole et al, 2018), in both independent and symbiotic states of the two organisms (Mendoza et al, 2016;Hortal et al, 2017;Lardi et al, 2017). Non-nodulating strains of Rhizobium leguminosarum compete with the nodulating types for infection sites, causing delay in development and function of root nodules (Lie et al, 1988), which reduces the performance of leguminous host plants (Gano-Cohen et al, 2016).…”
Section: Competitors Of Rhizobium Symbiosismentioning
confidence: 99%
“…Competition is the contentious interaction for limited resources between organisms that is characterized by efficient resource consumption (exploitation) or harmful effects to the adversary (interference) (Ghoul and Mitri, 2016). Competition for nutrients and space is a key form of antagonistic interaction that affects rhizobia and host plants (Postma et al, 1990;Poole et al, 2018), in both independent and symbiotic states of the two organisms (Mendoza et al, 2016;Hortal et al, 2017;Lardi et al, 2017). Non-nodulating strains of Rhizobium leguminosarum compete with the nodulating types for infection sites, causing delay in development and function of root nodules (Lie et al, 1988), which reduces the performance of leguminous host plants (Gano-Cohen et al, 2016).…”
Section: Competitors Of Rhizobium Symbiosismentioning
confidence: 99%
“…Facilitation of N uptake [ 21 ] and growth in grass-legume mixtures is the primary motivation for intercropping in pastoral agriculture. N and P fertilization can have varying effects on this relationship [ 57 ], as well as the length of time that species interact under particular nutrient conditions [ 58 ]. We successfully measured growth facilitation using HTP, revealing a yield benefit for both grasses and legumes ( Fig 3a ).…”
Section: Discussionmentioning
confidence: 99%
“…relationship [57], as well as the length of time that species interact under particular nutrient conditions [58]. We successfully measured growth facilitation using HTP, revealing a yield benefit for both grasses and legumes (Fig 3a).…”
Section: Plos Onementioning
confidence: 99%
“…On the other hand, P increases nodule mass. Work by Mendoza et al [23] has revealed that optimum supply of P triggers a positive growth response of legumes integrated with grass crops unlike pure stand. However, P may favor grass shoots and root biomass accumulation at the expense of the development of congregate legumes.…”
Section: Competition For Soil Nutrientsmentioning
confidence: 99%